A Randomized Comparison of Double Small, Standard, and Endoscopic Approaches for Carpal Tunnel Release. Issue 3 (September 2016) - Zhang, Xu; Huang, Xiangye; Wang, Xianhui; Wen, Shumin; Sun, Jianxin; Shao, Xinzhong
Abstract : Background: The purpose of this study was to introduce a new surgical technique of carpal tunnel release through double small incisions, and to compare the technique with the standard open release and endoscopic release. Methods: Two hundred and seven patients were allocated randomly into group A ( n = 73), B ( n = 65), or C ( n = 69). Patients in group A were treated with carpal tunnel release by means of double small incisions. Patients in group B were treated by means of the standard incision. Patients in group C had endoscopic release. Results: Preoperatively, the mean severity of symptoms of groups A, B, and C was 3.7 ± 0.58, 3.8 ± 0.62, and 3.7 ± 0.52, respectively; and the mean functional status was 3.2 ± 0.71, 3.2 ± 0.71, and 3.5 ± 0.64, respectively. At the final follow-up of 3 years, the mean severity of symptoms of the groups was 1.2 ± 0.45, 1.2 ± 0.31, and 1.5 ± 0.36, respectively; and the mean functional status was 1.2 ± 0.38, 1.2 ± 0.41, and 1.5 ± 0.42, respectively. Patient satisfaction was 95 ± 4.2, 90 ± 5.8, and 93 ± 4.4, respectively. There were no significant differences between groups regarding symptom severity or function status ( p > 0.05). For scar appearance, there were significant differences between groups A and B and between B and C, but not between A and C; for patient satisfaction, there were significant differences in all comparisons. Conclusions: Carpal tunnel release by means of double small incisions is a minimally invasive and less technically challenging procedure with good nerve visualization, resulting in good appearance of scars. CLINICAL QUESTION/LEVEL OF EVIDENCE: Therapeutic, II. Abstract : Supplemental Digital Content is available in the Text.Coding Perspective for this Article is on Page 646.